2011
DOI: 10.1016/j.ejcts.2010.11.045
|View full text |Cite
|
Sign up to set email alerts
|

The implication of vasa vasorum in surgical diseases of the aorta

Abstract: Vasa vasorum (VV) are microscopic vases that perfuse the vessel's wall; arteries and veins. Many recent researches support the opinion that VV have a significant role in aortic pathology. The VV, or 'the vessels of the vessels', form a network of microvessels that lie in the adventitia and penetrate the outer media of the host vessel wall. Although the importance of the VV in providing nutritional support is not well known, obstruction of blood flow through these vessels has been implicated in the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 87 publications
(137 reference statements)
2
19
0
Order By: Relevance
“…Though deemed as pathologically distinct entities, intramural hematoma may lead into acute aortic dissection, aneurysm or aortic rupture. 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though deemed as pathologically distinct entities, intramural hematoma may lead into acute aortic dissection, aneurysm or aortic rupture. 4 …”
Section: Discussionmentioning
confidence: 99%
“…4 Vaso vasorum vessels of vessels , forms network of vessels in adventitia, which also supply the outer media plays a significant role in pathogenesis of all aortic pathologies including intramural hematoma, aortic dissection and aortic aneurysm. 4 Animal studies have shown that aortic distensibility decreases when vaso vasorum are removed from the vessel wall. Penetrating atherosclerotic ulcer develops, when an atheromatous plaque, ulcerates through the internal elastic lamina and exposes the media to high-pressure aortic blood flow leading to intra medial hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…19-17). 38,41 The extent of IMH is classified by the Stanford approach as type A and type B. Class II is defined as IMH with hematoma formation within the medial layer.…”
Section: Classification Of Aortic Dissectionmentioning
confidence: 99%
“…These nerves have been shown to be associated with unique microvasculature, termed the vasa vasorum, in the adventitia (for review see [19]). This microvasculature has been implicated in plaque formation and associated with two neuro-inflammatory factors, substance P (SP) and calcitonin gene related peptide (CGRP) [19–21]. …”
Section: Introductionmentioning
confidence: 99%